(untitled) (Perner’s Contacts, 2024)
Cast (real) damascus steel (so-called “wootz”) is an ancient tool/weapon material. Due to relatively high carbon amounts, the wootz is hard to forge (or other hot-forming shaping). In some cases, the forging of wootz is impossible. During forging, cracks are often created that lead to absolutely disintegration of bulk material. In this paper is given one relationship between wootz microstructure and the forging impossibility.